Implementation of the inquiry learning model to enhance junior high school students’ scientific literacy: A qualitative study - Mizwar, Mizwar; Setiawan, Heri; Rogahang, Milan Kisy; Tikulembang, Garry Aditya (Priviet Social Sciences Journal, 2026)
This study aims to analyze the implementation of the inquiry learning model to enhance junior high school students’ scientific literacy. The research is grounded in the concern that Indonesian students’ scientific literacy remains low, largely due to traditional teaching methods focused on rote memorization rather than scientific exploration. Employing a qualitative descriptive approach with a case study design, the research was conducted at MTs Alkhairaat Pusat Palu. Data were collected through classroom observations, in-depth interviews, and document analysis, then processed using Miles, Huberman, and Saldaña’s interactive analysis model, which consists of data condensation, data display, and conclusion drawing. The results show that the guided inquiry learning model effectively promotes students’ active participation, strengthens their scientific reasoning abilities, and deepens their conceptual understanding of natural phenomena. The teacher acts as a facilitator, guiding students to construct knowledge through investigation and reflective discussion. Improvements in scientific literacy were evident in students’ ability to interpret experimental data, explain scientific phenomena logically, and connect scientific concepts with real-life contexts. Supporting factors included teacher readiness, the use of relevant contextual materials, and a collaborative learning environment. Theoretically, this study reinforces social constructivism as a foundation for inquiry-based science education, while practically, it provides recommendations for developing curricula and teacher training programs that emphasize evidence-based scientific investigation and inquiry-oriented pedagogy.